1995
DOI: 10.1029/94ja03232
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic storm effects in the low‐ to middle‐latitude upper thermosphere

Abstract: In this paper, we use data from the Dynamics Explorer 2 (DE 2) satellite and a theoretical simulation made by using the National Center for Atmospheric Research thermosphere/ionosphere general circulation model (NCAR‐TIGCM) to study storm‐induced changes in the structure of the upper thermosphere in the low‐ to middle‐latitude (20°‐40°N) region of the winter hemisphere. Our principal results are as follows: (1) The winds associated with the diurnal tide weaken during geomagnetic storms, causing primarily zonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
168
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(176 citation statements)
references
References 64 publications
7
168
0
1
Order By: Relevance
“…10a, b). The same result is con®rmed by numerous satellite observations of thermospheric composition at low to middle latitudes (Hedin et al, 1977;ProÈ lss, 1982;Burrage et al, 1992;Burns and Killeen, 1992;Burns et al, 1995b) as well as closer examination of [O] density by ground-based incoherent scatter and Fabry±Perrot measurements (Burnside et al, 1991). They show that the thermospheric response to a geomagnetic storm at low to middle latitudes consists of a quite moderate density increase of all atmospheric constituents, while the ratio…”
Section: Thermospheric Compositionsupporting
confidence: 59%
See 1 more Smart Citation
“…10a, b). The same result is con®rmed by numerous satellite observations of thermospheric composition at low to middle latitudes (Hedin et al, 1977;ProÈ lss, 1982;Burrage et al, 1992;Burns and Killeen, 1992;Burns et al, 1995b) as well as closer examination of [O] density by ground-based incoherent scatter and Fabry±Perrot measurements (Burnside et al, 1991). They show that the thermospheric response to a geomagnetic storm at low to middle latitudes consists of a quite moderate density increase of all atmospheric constituents, while the ratio…”
Section: Thermospheric Compositionsupporting
confidence: 59%
“…Zuzic et al (1997) Burns et al (1995a) may not be a salient feature of the disturbed thermosphere. ProÈ lss et al (1998) repeated the magnetic storm modelling of December 8, 1992 (Burns et al, 1995b) using both the TIGCM and the CTIM. They compared both simulations with neutral gas measurements of the Dynamics Explorer 2 satellite and found that both models significantly overestimate the increase in the O/N 2 density ratio at mid and low latitudes (on a constant pressure surface).…”
Section: Thermospheric Compositionmentioning
confidence: 99%
“…The negative storm effects occurred often during the main and recovery phases of storms (Abdu, 1997;Cander and Mihajlovic, 2005). Negative storm effects at high and middle latitudes are caused primarily by neutral composition changes due to the upwelling of molecular-rich air to higher altitudes driven by storm-time enhanced Joule heating (Mayr, Harris, and Spencer, 1978;Burns et al, 1995;Fuller-Rowell et al, 1994). The negative storm effects around the geomagnetic Equator are more closely related to changes in transportation caused by penetration electric fields (Lei et al, 2008c;Wang et al, 2010), as well as changes in neutral composition at later times during strong storms (Prölss, 1995;Buonsanto, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…An extensive bibliography exists on the response of the global thermosphere to geomagnetic disturbances. Examples of recent papers on the subject are those by Burns et al [1991Burns et al [ , 1995, and Fuller-Rowe# et al [1994,1996], who base their findings on general circulation model results. Numerous references to past work may be found in these papers.…”
Section: Introductionmentioning
confidence: 99%